Bakso daging sapi dengan penambahan rumput laut sebagai alternatif makanan tinggi serat dan yodium - Irmalawati Irmalawati; Rosi Novita (Politeknik Kesehatan Kemenkes Aceh, 2020)
Background: Seaweed is a low-level plant that has high nutritional value, such as protein, carbohydrates, fat, fiber and iodum. People really like the consumption of meatballs. The addition of seaweed to beef meatballs which increases the increase in better nutritional content with fiber and iodine content.Objectives: This study aims to develop a beef meatball formulation with the addition of seaweed as an alternative to foods high in fiber and iodine.Methods: The research design was an experiment through a completely randomized design. The time of the research was March 2019 and was carried out at the Food Technology Laboratory of the Nutrition Department and the Food Food Analysis Laboratory of the Faculty of Agriculture of Syiah Kuala. Panelists are trained nutrition alumni, totaling 25 people. Data were collected by interview, observation and checklist using an organoleptic questionnaire. Data were collected by interview and observation. The experimental formulations were FA = addition of 40% seaweed to beef meatballs, FB = 60% and FC = 80%. Statistical analysis using the Anova and Duncan test with 95% CI.Results: The results showed a significant effect of the addition of seaweed on the color (p= 0.000) and texture (p= 0.007) of beef meatballs. However, it had no effect on taste (p= 0.182) and aroma (p= 0.134). Chemically, seaweed meatball has a fiber content of 7.85% and an iodine content of 19.5%.Conclusion: The addition of seaweed to the manufacture of beef meatballs on the chemical properties of fiber and iodine has met SNI standards. The organoleptic results showed that the addition of seaweed had a significant effect on the color and texture of the beef meatballs, while the taste and aroma had no effect.